2011
DOI: 10.1093/jxb/err159
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic trafficking of wheat γ-gliadin and of its structural domains in tobacco cells, studied with fluorescent protein fusions

Abstract: Prolamins, the main storage proteins of wheat seeds, are synthesized and retained in the endoplasmic reticulum (ER) of the endosperm cells, where they accumulate in protein bodies (PBs) and are then exported to the storage vacuole. The mechanisms leading to these events are unresolved. To investigate this unconventional trafficking pathway, wheat γ-gliadin and its isolated repeated N-terminal and cysteine-rich C-terminal domains were fused to fluorescent proteins and expressed in tobacco leaf epidermal cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…Extensive and intensive research is being carried out on gluten proteins to determine their properties and structure. Based on their solubility in aqueous alcohol solutions, prolamins of wheat have been divided into two classes, the gliadins and glutenins (Francin-Allami et al, 2011). Together, gliadins and glutenins represent 80-85% of the total proteins of wheat flour (Veraverbeke and Delcour, 2002) and impart the unique properties-extensibility and elasticity to the wheat dough.…”
Section: Wheat Kernel Proteinsmentioning
confidence: 99%
“…Extensive and intensive research is being carried out on gluten proteins to determine their properties and structure. Based on their solubility in aqueous alcohol solutions, prolamins of wheat have been divided into two classes, the gliadins and glutenins (Francin-Allami et al, 2011). Together, gliadins and glutenins represent 80-85% of the total proteins of wheat flour (Veraverbeke and Delcour, 2002) and impart the unique properties-extensibility and elasticity to the wheat dough.…”
Section: Wheat Kernel Proteinsmentioning
confidence: 99%
“…Here, we have demonstrated that both a γ‐gliadin‐δ‐zein protein and a γ‐gliadin‐GFP fusion protein can accumulate to very high levels in transgenic tobacco. Previous studies demonstrated that when ectopically expressed in yeast or in tobacco BY‐2 cells, γ‐gliadin and γ‐gliadin fused to other proteins were transported to central vacuoles and degraded, probably due to lack of an ER retention signal (Francin‐Allami et al ., ; Rosenberg et al ., ). Napier et al .…”
Section: Discussionmentioning
confidence: 97%
“…[5][6][7][8]11,19) In addition, rice prolamin has been shown to form ER-derived PBs in plant tissues such as rice leaves, roots, 12) and calli.…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal domains of γ-zein and γ-gliadin are important for ER retention or the formation of ERderived PBs in heterologous tissue, and these domains are highly hydrophobic. 6,11) In addition to cereal prolamin, hydrophobic proteins such as hydrophobin (fungi) and elastin (mammalian) also formed PBs in a heterologous expression system. 22,23) These data suggest that the hydrophobic properties of the polypeptide promote aggregation in ER, resulting in the formation of ER-derived PBs.…”
Section: Discussionmentioning
confidence: 99%